Occupational Safety And Health Management, Workload, And Safety Behavior On Work Safety At PT. PLN (PERSERO) - Suryani Maryam; Rosali Sembiring; Fauzan Akbar Hasbiansyah (Jurnal Ekonomi, 2024)
Research aims: this study aims to investigate the effect of Occupational Safety and Health Management, Workload, and Safety Behavior on Work Safety. Design/Methodology/Approach: Drawing from the social exchange theory and flow theory, a theoretical framework was developed and tested using data collected from 80 PT. PLN (Persero) workers. A questionnaire survey was used to collect the data, while structural equation modeling (SEM) analysis was used as the data analysis approach. Research findings: The results reveal that both occupational safety and health management and safety behavior have a significantly positive impact on work safety amongst PT. PLN (Persero) workers and Workload do not affect Work Safety. Theoretical contribution/Originality: This study contributes to the Work safety literature by examining how work safety indicators such as occupational safety and health management affect work safety. In the context of PT. PLN (Persero) worker's occupational safety and health management is important, as the workers are frequently exposed to and threatened by serious work safety problems. Yet, there has been a paucity of research on the PT. PLN (Persero) sector to understand the relationship. Research limitation/implication: the study implies that when organizations are willing to improve occupational safety and health management, their employees will perceive improved work safety, and then will have more safety behavior and work safety.